Natural history and mid-term prognosis of severe tricuspid regurgitation: A cohort study - Samim, Daryoush; Praz, Fabien; Cochard, Baptiste; Brugger, Nicolas; Ruberti, Andrea; Bartkowiak, Joanna; Corpataux, Noé; Reineke, David; Pilgrim, Thomas; Windecker, Stephan; Wenaweser, Peter Martin; Wild, Mirjam G. (Frontiers in Cardiovascular Medicine, 2023)
Objectives: The objective of this study was to characterize a population of patients with severe tricuspid regurgitation (TR) evaluated at a tertiary care center, assess mid-term clinical outcomes, and identify prognostic factors. Background: The impact of TR on morbidity and mortality is increasingly recognized. Clinical characteristics and long-term outcomes of patients suffering from TR remain unclear. Methods: This is a retrospective observational single-center study from a tertiary care hospital including patients with echocardiographic diagnosis of severe TR between January 2017 and December 2018. We used the Kaplan-Meier method to estimate survival for up to 4 years. After excluding patients with tricuspid valve intervention and surgery during follow-up, a multivariate analysis was performed to assess predictors of 2-year mortality using the Cox regression model. Results: A total of 278 patients (mean age 74.9 ± 13.7 years, 47.8% female) with severe TR were included in the study. The majority (83.1%; n=231) had secondary TR. Comorbidities such as atrial fibrillation (AFib) (68.0%; n=189), severe renal failure (44.2%; n=123), pulmonary hypertension (80.9%; n=225) and right ventricular (RV) dysfunction (59.7%; n=166) were highly prevalent. More than half of patients with a cardiac implantable electronic device (CIED) (54.3%; n=44) showed echocardiographic signs of lead-leaflet interaction causing or contributing to TR. The estimated 2- and 4-year all-cause mortality was 50% and 69%, respectively. Using multivariate analysis, age, severe renal failure, heart failure with reduced ejection fraction (HFrEF), and vena contracta width ≥14mm were identified as predictors of 2-year mortality. Nine percent (n=25) of the study cohort underwent transcatheter or surgical treatment for TR during follow-up. Conclusions: Our study shows the high burden of morbidity and the dismal survival of patients with severe TR. It also highlights the extent of the therapeutic need, since the vast majority of patients were left untreated. Additionally, CIED RV lead-associated TR was prevalent suggesting a need for more attention in clinical routine and research.